Caracterización de los médicos que realizan investigación científica registrados en el RENACYT. Un estudio transversal en Perú - Herrera-Añazco, Percy (2024)
Objective: To describe the characteristics of physicians who conduct scientific research in Peru who are registered in RENACYT (Peruvian National Researcher Network). Material and methods: A descriptive, cross-sectional study was performed using the Researcher Registry at the National System of Science, Technology, and Technological Innovation, the National Registry of Academic Degrees and Professional Titles, and the database of the Peruvian Medical Association (PMA). We included sociodemographic, academic, and job variables, and a bivariate analysis was performed according to the physician's place of registration and gender. Results: We evaluated 723 physicians, representing 10.5% of the total number of researchers and 0.75% of qualified physicians registered in the PMA. Most were registered in Lima (74.41%), 56.85% had a master’s degree, and 28.49% had a PhD degree. According to the 2021 classification of researchers, level III was the most frequent (12.03%). Three-quarters (76%) were medical school teachers, and 46.2% were thesis advisors. The median number of papers published in SCOPUS-indexed journals was 9.5, while the median h-index was 4. Compared to physicians from provinces, those from Lima had more experience as thesis advisors (80.21% vs. 19.79%, p < 0.001), had a PhD degree (77.18% vs. 22.82%, p = 0.007), had more papers published (11 vs. 7, p < 0.001) and a higher h-index (4 vs. 3, p < 0.001). Conclusions: There is disparity in the number of physicians who conduct scientific research in Lima and provinces, with differences in work experience and scientific production.